2013
DOI: 10.1167/iovs.12-11496
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Text Type on Near Work–Induced Contrast Adaptation in Myopic and Emmetropic Young Adults

Abstract: PURPOSE. Contrast adaptation has been speculated to be an error signal for emmetropization. Myopic children exhibit higher contrast adaptation than emmetropic children. This study aimed to determine whether contrast adaptation varies with the type of text viewed by emmetropic and myopic young adults.METHODS. Baseline contrast sensitivity was determined in 25 emmetropic and 25 spectacle-corrected myopic young adults for 0.5, 1.2, 2.7, 4.4, and 6.2 cycles per degree (cpd) horizontal sine wave gratings. The adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Thus, there was no need to interpret or attach meaning to the symbols. Under these circumstances, accommodation to Chinese and Latin characters showed no significant differences over the stimulus range zero to 5.00 D. This implies that any differences in accommodation caused by the differing cognitive demands of the two types of text in the reading tasks used by Yeo, Atchison and Schmid must be small. A key point in both studies is that there is no evidence that lags of accommodation are greater with Chinese compared to Latin characters, so that it seems unlikely that the greater levels of myopia observed among ethnic Chinese are related to differences in accommodative lags associated with the form of characters of the reading texts used in childhood.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Thus, there was no need to interpret or attach meaning to the symbols. Under these circumstances, accommodation to Chinese and Latin characters showed no significant differences over the stimulus range zero to 5.00 D. This implies that any differences in accommodation caused by the differing cognitive demands of the two types of text in the reading tasks used by Yeo, Atchison and Schmid must be small. A key point in both studies is that there is no evidence that lags of accommodation are greater with Chinese compared to Latin characters, so that it seems unlikely that the greater levels of myopia observed among ethnic Chinese are related to differences in accommodative lags associated with the form of characters of the reading texts used in childhood.…”
Section: Discussionmentioning
confidence: 83%
“…In the only comparable study, using a larger number of subjects (n = 83), Yeo, Atchison and Schmid found that mean accommodative lags (around 1.00 D) in both emmetropic and myopic Chinese children during binocular reading tasks at stimulus levels of 3.00 and 4.00 D were lower for Chinese characters, when compared to those for Latin characters by modest amounts (less than 0.05 D), which were statistically but not clinically, significant. For these stimuli, the present data gave overall mean lags of 1.00 ± 0.63 D for Chinese characters and 1.05 ± 0.62 D for Latin characters.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations